Securing water for all: managing physical and economic scarcity in the Anthropocene poster - Jampani, Mahesh; Müller, A. B.; Gebrechorkos, S. H. (2024)
The Anthropocene, characterized by significant human impacts, raises unprecedented water management challenges due to physical and economic water scarcity. Climate change exacerbates the problem by altering the hydrological cycle and increasing extreme events' frequency. Physical water scarcity concerns insufficient water to meet human and environmental needs, while economic scarcity results from infrastructure and financial deficiencies. This session explores the complex dynamics of water scarcity and its interconnectedness with hydrology, climate, pollution, health, and resource allocation, highlighting solutions and research gaps.